2020
DOI: 10.3390/buildings10120241
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Seismic Isolation for Buildings Founded on Soft Soil. Case Study of a RC Building in Shanghai

Abstract: Base (seismic) isolation is a promising technology for seismic protection of buildings and other constructions. Nowadays, it is accepted that such a technique is efficient and reliable; however, it has two major limitations: soft foundation soil, and tall buildings. The first issue restrains the seismic isolation spreading, given that soft soil is frequent in densely populated areas, and usually such a soil type concentrates the highest seismicity levels. This paper aims to contribute to demonstrating that bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
(15 reference statements)
0
0
0
Order By: Relevance
“…It should be mentioned that the foundation compliance and kinematic soil-structure interaction were not considered for the simplicity of the analysis. Almansa et al [60] investigated the performance of a rubber-isolated six-story RC building in soft soil. They concluded that the soil-structure interaction effect is rather negligible in the case of isolated buildings.…”
Section: Structural Modelingmentioning
confidence: 99%
“…It should be mentioned that the foundation compliance and kinematic soil-structure interaction were not considered for the simplicity of the analysis. Almansa et al [60] investigated the performance of a rubber-isolated six-story RC building in soft soil. They concluded that the soil-structure interaction effect is rather negligible in the case of isolated buildings.…”
Section: Structural Modelingmentioning
confidence: 99%
“…The growing popularity of the seismic isolation technology is primarily attributed to its ability to isolate the majority of the energy from earthquakes by extending buildings' natural period [1][2][3]. However, recent research suggests that the efficacy of isolators diminishes under long-period pulse-type earthquakes [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…By comparison with the conventional seismic design approach, which is based on an increased strengthening of the structures, the seismic isolation concept is aimed at a significant reduction in dynamic response induced by the earthquake. To date, extensive isolation devices, including rubber bearings (RB), lead plug rubber bearings (LRB), frictional-sliding bearings, and roller bearings, have been developed [19][20][21][22][23]. Though those isolation bearings have been applied to the area of base isolation, the application of the seismic isolation devices into the staircases is still rare.…”
Section: Introductionmentioning
confidence: 99%